2002
DOI: 10.1021/jf0200422
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Calcium Fumarate Salts Is Equivalent to Other Calcium Salts When Measured in the Rat Model

Abstract: Calcium absorption from fumarate salts (calcium fumarate and calcium malate fumarate), which have recently been considered for use as sources for food and beverage enrichment, was compared to that from calcium citrate malate, calcium citrate, and calcium carbonate. Salts were instrinsically labeled with 45Ca and orally administered to Sprague-Dawley rats. Fractional absorption of calcium from each salt was determined using the femur uptake model. Fractional absorption from the five salts (0.30-0.27) was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…However, there are contradictory reports (Couzy et al, 1995;Kohls & Kies, 1992) in the literature showing no difference in the bioavailability of calcium. Weaver, Martin, Costa, Saleeb, and Huth (2002) also did not observe any significant differences in fractional absorption from five calcium salts in rat model. No clear difference has been observed in the efficiency of calcium absorption between skimmed milk and calcium-enriched skim milk using isotope technique in human subjects (Fairweather-Tait et al, 1989).…”
Section: Bioavailability Of Calcium From Calcium-fortified Milkmentioning
confidence: 62%
“…However, there are contradictory reports (Couzy et al, 1995;Kohls & Kies, 1992) in the literature showing no difference in the bioavailability of calcium. Weaver, Martin, Costa, Saleeb, and Huth (2002) also did not observe any significant differences in fractional absorption from five calcium salts in rat model. No clear difference has been observed in the efficiency of calcium absorption between skimmed milk and calcium-enriched skim milk using isotope technique in human subjects (Fairweather-Tait et al, 1989).…”
Section: Bioavailability Of Calcium From Calcium-fortified Milkmentioning
confidence: 62%
“…(51)(52)(53) The enhanced retention results might be attributed to the low calcium acclimation diet used and the use of direct administration via gelatin capsules. (54) The effect of the different polymorph compositions also may be attributed to high retention, especially in the CCC preparation, comprising a mixture of vaterite and calcite.…”
Section: Discussionmentioning
confidence: 99%
“…While difficult to compare between different calcium formulations with or without a reference salt, the retention values obtained in this study are as high as those observed for calcium ascorbate (50) and higher than those reported for other calcium formulations, such as calcium lactate, fumarate, citrate, citrate-malate, carbonate, and TBE. (34,51,52) Moreover, when considering the effectiveness of dietary calcium sources, one also must take into account the relatively low elemental calcium content of these formulations. In this respect, ACC contains a relatively high elemental calcium content of 33%, as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7] The calcium absorbability from diets or its elements is traditionally defined to be the quantity of calcium in the blood, urine or body compartments, particularly bone, after multiple administrations or ingestions over several days, and its extent is defined as absorption, fractional absorption, or nutrient bioavailability of calcium, measured usually by mass balance techniques. [8][9][10][11] Studies have shown that calcium absorbability is as low as 20-40% after calcium salt administration, [9][10][11][12] and many modern diets do not provide the recommended levels of calcium (400-1,200 mg/day). 12) Thus, dietary calcium supplements have been recommended for prevention of calcium related diseases, and various calcium salts including calcium carbonate and calcium lactate have been examined as calcium supplement sources.…”
Section: Introductionmentioning
confidence: 99%